From Epiphylogenesis to General Organology - Robert Alexander Gorny; Andrej Radman (Footprint)
Epiphylogenesis is a neologism coined under Stiegler’s anthropotechnical theorisation of the co-evolution of brains and tools. In line with feminist and decolonial theorists like Claire Colebrook and Kathryn Yusoff, it foregrounds that there has never been such a thing as ‘the human’. There are only differentiation processes that historically make humans who they are, and do so in different ways. As such, it has gained some currency in a stream of neo-materialist theories that have revisited anthropogenesis, or the quasi-causality of becoming human, that operates by way of progressively differentiating environments and technics. In addition to primary memory as the genetic information expressed in DNA and secondary memory acquired epigenetically through a complex nervous system, there is also tertiary memory, which Stiegler named ‘epiphylogenetic’. It is the accumulation and retention of historical epigenetic differentiations within the spatio-temporal organisation of material environments. Specifically, the formation of organisational technics includes writing, art, clothing, tools, and machines, but also architecture and urban planning. This outsourcing of memory from the organic changes the conditions for further phylogenetic becomings, given that evolutions continue to be extrinsically organised (‘ex-organised’) by associated technicised milieus.